2008
DOI: 10.1093/brain/awn100
|View full text |Cite
|
Sign up to set email alerts
|

Short-latency median-nerve somatosensory-evoked potentials and induced gamma-oscillations in humans

Abstract: Recent studies have suggested that cortical gamma-oscillations are tightly linked with various forms of physiological activity. In the present study, the dynamic changes of intracranially recorded median-nerve somatosensory-evoked potentials (SEPs) and somatosensory-induced gamma-oscillations were animated on a three-dimensional MR image, and the temporal and spatial characteristics of these activities were analysed in 10 children being evaluated for epilepsy surgery. Visual and quantitative assessments reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 75 publications
(127 citation statements)
references
References 47 publications
5
121
1
Order By: Relevance
“…However, the possibility that GBOs reflect cortical activity that is specific for the processing of somatosensory input, but not specific for the processing of nociceptive input should not be dismissed. Indeed, several studies have shown that non-nociceptive somatosensory stimuli also elicit GBOs within SI (Chen and Herrmann, 2001;Bauer et al, 2006;Fukuda et al, 2008). Hence, nociceptive and non-nociceptive somatosensory GBOs could reflect similar cortical responses, involved in the initial selection and preferential processing of somatosensory stimuli regardless of whether they are nociceptive.…”
Section: Neural Origin and Functional Significance Of Laser-induced Gbosmentioning
confidence: 99%
“…However, the possibility that GBOs reflect cortical activity that is specific for the processing of somatosensory input, but not specific for the processing of nociceptive input should not be dismissed. Indeed, several studies have shown that non-nociceptive somatosensory stimuli also elicit GBOs within SI (Chen and Herrmann, 2001;Bauer et al, 2006;Fukuda et al, 2008). Hence, nociceptive and non-nociceptive somatosensory GBOs could reflect similar cortical responses, involved in the initial selection and preferential processing of somatosensory stimuli regardless of whether they are nociceptive.…”
Section: Neural Origin and Functional Significance Of Laser-induced Gbosmentioning
confidence: 99%
“…Inspection of the data showed clear N20m and induced activity in beta as well as low and high gamma bands as also previously reported (Fukuda et al, 2008(Fukuda et al, , 2010Hagiwara et al, 2010). Lack of effects of treatments on N20m is in line with previous results (Pierantozzi et al, 1999;Priori et 4.3 Study II al., 2001;Conte et al, 2010;Airaksinen et al, 2011) although some of these earlier studies may be partly confounded by methodological issues.…”
Section: Study I Differentiated Effects Of Deep Brain Stimulation Andsupporting
confidence: 89%
“…Median nerve stimulation and the subsequent oscillatory dynamics such as somatosensory evoked fields (SEF) or potentials (SEP) are effective tools to study somatosensory processing (Gaetz and Cheyne, 2003;Fukuda et al, 2008Fukuda et al, , 2010. Median nerve stimulation involves placing a bipolar stimulation electrode near the wrist, where the median nerve runs superficially and stimulating it with a current of 2-15 mA and with a pulse width of 150 μ s. The sign of a stimulated nerve is a visible twitch of the thumb.…”
Section: Oscillations In Sensory Cortexmentioning
confidence: 99%
See 2 more Smart Citations